PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN BERKUNJUNG PADA WISATA PANTAI GILI NOKO DI BAWEAN - Vita Nur Jannah; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT  This study aims to determine and analyze the effect of service marketing mix simultaneously and partially to the decision to visit the Gili Noko Beach tourism in Bawean. The method used is purposive sampling technique where the technique of determining the sample with consideration of certain criteria. The analysis technique used is descriptive quantitative by using Likert scale, multiple linear regression analysis, coefficient of determination and also through f test and t test by using SPSS program.Based on the results of data analysis simultaneously shows that the influence of product variables, price, location, promotion, employees, process and physical evidence have a significant influence on the decision to visit on Gili Noko beach tour in Bawean. While the partial variable of product, price, location, employee, process, and physical evidence have no significant effect to the decision of visiting on Gili Noko beach tourism in Bawean. And for the promotion variable has a significant influence on the decision to visit on Gili Noko Beach tour in Bawean. Keywords: Marketing Mix, Visit Decision.